2018
DOI: 10.1016/j.polymer.2018.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the nanostructure of epoxy resins: Reaction selectivity and stoichiometry

Abstract: The internal topology of epoxy resins is, for the first time, shown not to be the determining factor for small molecule transport. Whilst epoxy resins comprise the matrix component of many high performance composites, coatings and adhesives, the nanostructure and transport properties of these materials are not well understood. Here, peakforce AFM imaging, in-situ FTIR cure analysis and nanochemical AFM-IR imaging are used to establish the effects of reaction selectivity and stoichiometry on the nanostructure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…While most of the early studies on the reaction between DGEBA and bisphenol A (BPA) have focused on understanding the kinetics of linear chain formation and branching in the presence of a basic catalyst, 15–17 more recent studies have focused on the properties of the final thermosets. Morsch et al performed nano‐chemical imaging and nano‐thermal analysis on the networks formed by DGEBA, THPE and BPA and correlated the cross‐linking density to the water uptake and heterogeneities in the network structure 18–20 . Heise et al found that a range of cross‐linking densities and glass transition ( T g ) temperatures can be achieved by varying the BPA concentration 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the early studies on the reaction between DGEBA and bisphenol A (BPA) have focused on understanding the kinetics of linear chain formation and branching in the presence of a basic catalyst, 15–17 more recent studies have focused on the properties of the final thermosets. Morsch et al performed nano‐chemical imaging and nano‐thermal analysis on the networks formed by DGEBA, THPE and BPA and correlated the cross‐linking density to the water uptake and heterogeneities in the network structure 18–20 . Heise et al found that a range of cross‐linking densities and glass transition ( T g ) temperatures can be achieved by varying the BPA concentration 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Morsch et al performed nano-chemical imaging and nano-thermal analysis on the networks formed by DGEBA, THPE and BPA and correlated the cross-linking density to the water uptake and heterogeneities in the network structure. [18][19][20] Heise et al found that a range of cross-linking densities and glass transition (T g ) temperatures can be achieved by varying the BPA concentration. 21 The T g values of base (imidazole) catalyzed DGEBA-BPA thermosets ranged from 60-80 C when the BPA concentration was varied from 50-25 mol%.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis of nanodomains in polymer-based materials that relates chemical composition and localized thermal properties can be carried out using this approach. 45,48 AFM-IR has been used to confirm the uniformity of the polymerization reaction of PEDOT 49 and P3HT. 50 CNT-reinforced thermoset composites have been investigated revealing the distribution of chemical interfaces.…”
Section: Infrared and Raman Spectroscopies With Scanning Probe Micros...mentioning
confidence: 99%
“…Especially, with the development of miniaturization and high power of electronic devices and motors, efficient heat management is becoming a critical issue. [4][5][6][7] Generally, there are two methods to increase the thermal conductivity of epoxy resin: chemical 8,9 and physical [10][11][12][13][14][15][16] ways. The chemical method is designed for the epoxy resin molecular structure, and the improvement of its thermal conductivity is limited and high cost.…”
Section: Introductionmentioning
confidence: 99%